Thiolated gelatin films: Renaissance of gelatin as sustained intraoral dosage form. (February 2017) - Rohrer, Julia; Partenhauser, Alexandra; Zupančič, Ožbej; Leonavičiūtė, Gintarė; Podričnik, Snežana; Bernkop-Schnürch, Andreas
Graphical abstract: Highlights: A highly potent entirely S-protected thiolated gelatin was synthesized. Non-in-the-mouth-melting visco-elastic properties of the novel matrix were evident. Bucco-adhesive films with a residence time of up to 8 h were formulated. Abstract: The aim of this study was the design and evaluation of an entirely S-protected thiomer as matrix for intraorally administered films. The highly bucco-adhesive gelatin thiomer was designed based on the ligand cysteamine which was connected via disulfide bond with the aromatic leaving group 2-mercaptopyrimidine-4, 6-diol (2-MPD). The thiol ligand cysteamine 2-MPD (Cys-2-MPD) was synthesized via the coupling of dimerised 2-MPD to cysteamine (Cys) and then attached to gelatin scaffold via a carbodiimide mediated reaction. The entirely S-protected thiomer (gelatin-Cys-2-MPD) was characterized with respect to its thiolation efficiency, safety, melting point and mucoadhesive features. Thiomer films were prepared and assessed for in vitro dislodgement stress via rotating cylinder and tensile studies on porcine buccal mucosa. Gelatin-Cys-2-MPD showed a coupling rate of 392 ± 41 μmol 2-MPD per gram polymer and provides 100% protection efficiency of total amount of attached sulfhydryl groups. The cytotoxic safety profile provided a survival rate of over 90% after 24 h of incubation. Mucoadhesive features assessed via rheological investigations of mucus-polymer mixtures showed an up to 4-fold increased polymer mucus interaction in comparison to non-thiolated control (p < 0.05 ∗ 10 −4 ). In-vitro rotating cylinder studies recorded nearly 20-times extended residence time of entirely S-protected buccal films in comparison to non-thiolated control as well as up to 26-fold increased total work of adhesion (TWA) (p < 0.04 ∗ 10 −3 ) was evident for the thiomer. Being highly bucco-adhesive, the novel designed entirely S-protected gelatin features highly mucoadhesive properties which are beneficial for intraorally applied films.